RNA-seq analysis of testes from flurochloridone-treated rats. (23rd March 2020) - Zhou, Su; Li, Rui; Hou, Wanwan; Wang, Yue; Zhang, Suhui; Yu, Ying; Zhang, Lei; Zhu, Hongyan; Zhang, Zhichao; Fang, Jing; Chang, Xiuli; Zhang, Yubin; et al.
Abstract: Flurochloridone (FLC) is a widely used herbicide in developing countries. Although the testes are a target organ for FLC in rats, the adverse effects of FLC on testes have not been fully elucidated. To clarify them, we performed RNA-seq analysis using the testes of FLC-treated rats from our previous subchronic toxicity tests. Unilateral testes of three male rats from solvent control groupand three FLC-treated groups (3 mg/kg, 31.25 mg/kg and 125 mg/kg) were used for RNA extraction. A poly A selection protocol coupled with an Illumina TruSeq RNA-Seq library protocol was used to construct RNA-Seq libraries. Principal component analysis (PCA), differentially expressed gene (DEG) analysis, and hierarchical clustering analysis (HCA) were conducted using R. Gene Ontology (GO) term enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were performed to understand the biological characteristics of the DEGs using the Database for Annotation, Visualization and Integrated Discovery (DAVID). The results indicated that many up-regulated DEGs were enriched in pathways associated with testicular injury, such as mitogen-activated protein kinase (MAPK) signaling, lysosome and focal adhesion. Many down-regulated DEGs were enriched in pathways associated with testicular reproduction function, such as sexual reproduction, spermatogenesis and germ cell development. Moreover, we confirmed the oral no-observed-adverse-effect level (NOAEL) of 3 mg/kg in subchronic toxicity test, because the overall testicular gene expression in 3 mg/kg FLC-treated group was similar to that of the solvent control group. In 31.25 mg/kg and 125 mg/kg groups, DEGs revealed that testicular injury was related to oxidative stress.